2020
DOI: 10.1016/j.dib.2020.106139
|View full text |Cite
|
Sign up to set email alerts
|

Electronic nose dataset for pork adulteration in beef

Abstract: This article provides a dataset of several weight combinations from the adulteration of pork in beef using an electronic nose (e-nose). Seven combinations mixtures have been built, they were 100% pure beef, 10% mixed with pork, 25% mixed with pork, 50% mixed with pork, 75% mixed with pork, 90% mixed with pork, and 100% pure pork. By using this combination, a minimum of 10% of a mixture of pork or beef can be detected. In each experiment cycle, data were collected for 120 s using an e-nose. The availability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…The data of all 7 classes are shown in TABLE 3. For interested readers, our dataset has also been uploaded here [43], [44].…”
Section: A Materialsmentioning
confidence: 99%
“…The data of all 7 classes are shown in TABLE 3. For interested readers, our dataset has also been uploaded here [43], [44].…”
Section: A Materialsmentioning
confidence: 99%
“…The meat samples were separately minced and artificially adulterated to four adulteration levels: 100% 97%, 95% and 90% w / w of turkey to have a total of 20 g per sample (meat mixture concentration). The concentration levels for this study were determined based on the commonly reported ranges in literature [ 7 , 8 , 9 ] but the extra lower level of 97% w / w turkey (3% w / w of chicken in turkey) was included to study the feasibility of e-tongue in discriminating lower concentrations than those reported in literature.…”
Section: Methodsmentioning
confidence: 99%
“…This type of adulteration be done at varying concentration levels of meat types depending on the meat type and market demand. Concentration levels with increasing scales of 5% w / w [ 7 ], 10% w / w [ 8 ], and 20% w / w [ 9 ] of meat adulteration are among the most common in literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially, we can describe GD optimization as a hiker (the weight coefficient) who wants to climb down a mountain (cost function) into valley (cost minimum) and each step is determined by the steepness of the slope (gradient) and the leg length of the hiker (learning rate). Commonly, in deep learning, stochastic GD is used as a learning algorithm (Hinton et al, 2012;Hua et al, 2015;Sarno et al, 2020). Furthermore, gradient value can be obtained by curve fitting.…”
Section: Related Workmentioning
confidence: 99%